Fifteen new species of Chilicola (Oroediscelis) (Hymenoptera: Colletidae: Xeromelissinae) with illustrated keys to the males and females of the subgenus - Packer, Laurence; Dumesh, Sheila (Zootaxa, 2019)
Fifteen new species of Chilicola subgenus Oroediscelis are described and illustrated. The following 11 species are from Argentina recording a remarkable diversity and the first records of the subgenus in the country: Chilicola capillitas Packer and Dumesh, new species, C. abrebotellas, Packer and Dumesh, new species; C. goloboffi Packer and Dumesh, new species; C. fritzi, Packer and Dumesh, new species; C. rozeni Packer and Dumesh, new species; C. roigi Packer and Dumesh, new species; C. carpenteri Packer & Dumesh, new species; C. calchaqui Packer and Dumesh, new species; C. jaguense Packer and Dumesh, new species; C. cuyense Dumesh & Packer, new species; and C. huarpe Packer and Dumesh, new species. Chilicola pustulata Packer and Dumesh, new species, and Chilicola luna Dumesh, and Packer new species, are described from Peru; C. boharti Packer and Dumesh, new species, and C. ashei Dumesh and Packer, new species, are described from Bolivia, where C. carpenteri also occurs. An unusual feature of the male antennae is described: long setae on F2 and F3 (less commonly F4) that are appressed to, and occasionally longer than, the succeeding flagellomere. Additional records for previously described species are listed and a revised key to males is provided as well as a provisional complete key for all females.